Twentieth Century Winter Changes in Southern Hemisphere Synoptic Weather Modes - Jorgen S. Frederiksen; Carsten S. Frederiksen (Advances in Meteorology)
During the last sixty years, there have been large changes in the southern hemisphere winter circulation and reductions in rainfall particularly in the southern Australian region. Here we examine the corresponding changes in dynamical modes of variability ranging from storm tracks, onset-of-blocking modes, northwest cloud-band disturbances, Antarctic low-frequency modes, intraseasonal oscillations, and African easterly waves. Our study is performed using a global two-level primitive equation instability-model with reanalyzed observed July three-dimensional basic states for the periods 1949–1968, 1975–1994, and 1997–2006. We relate the reduction in the winter rainfall in the southwest of Western Australia since the mid-1970s and in south-eastern Australia since the mid-1990s to changes in growth rate and structures of leading storm track and blocking modes. We find that cyclogenesis and onset-of-blocking modes growing on the subtropical jet have significantly reduced growth rates in the latter periods. On the other hand there is a significant increase in the growth rate of northwest cloud-band modes and intraseasonal oscillation disturbances that cross Australia and are shown to be related to recent positive trends in winter rainfall over northwest Western Australia and central Australia, in general. The implications of our findings are discussed.